The Effect of Distance Running on the Anthropometry and Body Functions for the Elderly: 長跑運動對老年人體型、身體機能和素質狀況影響的研究 - GU, Liyan; YOU, Guijie; ZHANG, Yiming; ZHANG, Lan (Asian Journal of Physical Education & Recreation, 2000)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. Because of the population of the old people is increasing remarkably in today’s society, due to the development of the standard of medical science and technique, there is the positive significance in improving old people’s physique and health by understanding their present constitutional situation and health condition, and in studying in aging regulations and the function of anti-aging by doing exercise. The article has tested the function and sports quality of the subjects, part of whom are the retired staffs in some universities in Beijing, and others are the members of the Jogging Club of Old People. It is manifested that Most of the indexes in function and sports quality were significant better in aerobic exercise group than in common group no matter of males or females. It is concluded that longterm regular aerobic exercise can slow down the declining speed of cardio-pulmonary function, and maintain and improve the sports quality of old people. 隨著人類社會進步和醫療科技的發展，人口老齡化已成為世界人口發展的必然趨勢。所以瞭解老年人的身體機能和素質，對研究衰老規律和運動抗衰老的作用，全面提高中國老年人體質與健康水平具有積極的意義。本文將227名北京部分高校退休敎職工和北京市老年長跑俱樂部的隊員，按受試者鍛煉和訓練情況劃分為普通組和有氧運動組，對他們進行了形態、身體機能和運動素質的測試。結果顯示，有氧組和普通組在形態、身體機能和運動素質的大多數指標上存在明顯差異，表現為，有氧運動組的形態、身體機能和素質等指標明顯優於普通組。這就説明長期堅持有氧運動對於減緩心肺功能下降的速度，維持和提高老年群體身體素質有積極的促進作用。